Spain at War : a monthly journal of facts and pictures. No. 5 - Barron, Richard ; Dickinson, Thorold ; Nicholas, T. E. (Thomas Evan) ; Bartlett, Reg; Duff, Charles, 1894-1966 (London : United Editorial Limited)
1938-04 SA15-016-001 44 pages 15X/1/293/2